To Condemn or Not to Condemn: Perceived Climates Concerning Sexual Orientation in Black Churches. (9th July 2021) - Young, Luther
Abstract: Although the United States is becoming more accepting of lesbian, gay, bisexual, and queer (LGBQ) identities, black people are still more likely than the general population to disapprove of non-heterosexuality. Previous research points to the conservative views of the Black Church as a potential explanation for this disparity, but few studies have considered the diversity of perspectives within the Black Church. Drawing upon in-depth interviews with black Christians, this article examines how black congregants experience their churches' climates concerning sexual orientation. Findings suggest that black congregations tend to foster climates that are not affirming of non-heterosexuality; however, they vary in how they demonstrate non-affirmation. Furthermore, the study finds considerable differences in how congregants perceive and make sense of their perceived church climates concerning non-heterosexuality. These results suggest that the Black Church is not monolithic in its stance concerning sexuality and have implications for efforts to promote LGBQ inclusion within congregations.